2020
DOI: 10.3390/en14010169
|View full text |Cite
|
Sign up to set email alerts
|

Study of Renewable Energy Penetration on a Benchmark Generation and Transmission System

Abstract: Significant changes in conventional generator operation and transmission system planning will be required to accommodate increasing solar photovoltaic (PV) penetration. There is a limit to the maximum amount of solar that can be connected in a service area without the need for significant upgrades to the existing generation and transmission infrastructure. This study proposes a framework for analyzing the impact of increasing solar penetration on generation and transmission networks while considering the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Regarding the gender of household heads, ecofeminism suggests that women are more active than men regarding environmental issues for various social, cultural, and biological reasons [49]. For instance, Akeyo et al [50] found that renewable energy development is supported by about 90% of women compared to 60% of men. By contrast, another study showed that men were likelier to adopt new technologies than women [51].…”
Section: Determinants Of Household Solar Energy Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the gender of household heads, ecofeminism suggests that women are more active than men regarding environmental issues for various social, cultural, and biological reasons [49]. For instance, Akeyo et al [50] found that renewable energy development is supported by about 90% of women compared to 60% of men. By contrast, another study showed that men were likelier to adopt new technologies than women [51].…”
Section: Determinants Of Household Solar Energy Adoptionmentioning
confidence: 99%
“…However, a systematic review across sub-Saharan Africa indicated that the adoption of solar energy technologies might reproduce the structures that determine power and resource allocation at the local level, such as control over resources, gendered division of labor, and gendered domestic space, with implications for women who have to perform household chores [57]. Furthermore, previous studies found that women are more willing to pay or support renewable energy technologies because it will ease their burden on the long hours spent gathering fuel wood and also reduce their exposure to indoor air pollution [12,50,53]. The situation in the case of Seychelles is also unique because it's more about decision-making in a context where all households already have access to electricity-a contrary scenario to what prevails in most developing countries and Africa in particular.…”
Section: Gender and Age Of Household Headmentioning
confidence: 99%
“…The fuel commonly used for power generation is in the form of fossil fuels such as coal and petroleum, which has caused its rapid depletion and various other environmental concerns. This has motivated the scientists to integrate the renewable energy sources and reduce the transmission and distribution losses to fulfill the needs of the industry and society [1][2][3]. To maintain the balance of power between the supply and load, the coordination of these sources such as wind and solar along with their control is an essential part of a microgrid.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the increase in DERs, Photovoltaic (PV) generation systems are shown to be the most effective DER prospect for LVDGs [4]. However, since the conventional LVDG was designed based on the assumption that power flow would be from the primary substation to the loads [5], high PV penetration gives rise to unforeseen problems [6]. The high penetration of rooftop PV in LVDGs can result in reverse power flows [7] and an increase in the neutral current, leading to distribution and transformer losses due to overheating of the conductor [5,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%